2005
DOI: 10.1111/j.1471-0528.2005.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

General obstetrics: The kinetics of routine antenatal prophylactic intramuscular injections of polyclonal anti‐D immunoglobulin

Abstract: Objective To observe the pharmacokinetics of intramuscular anti-D immunoglobulin (IgG) given for routine antenatal prophylaxis.Design Prospective observational study.Setting Maternity unit and antenatal serology laboratory in a district teaching hospital.Population Forty-five rhesus-D-negative pregnant women not sensitised to RhD. Results For the 43 women in whom serial data were collected, there were no detectable differences between pregnancies with an RhD-positive (26) or -negative (17) fetus. Maximum IgG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 16 publications
8
21
1
5
Order By: Relevance
“…The postmaturity risk factor might be explained by insufficient levels of preventive anti‐D Ig, after a single gift of 1000 iu (200 μg) in week 30 of pregnancy, in addition to the obvious immunogenic effect of prolonged exposure to fetal cells. Several studies showed undetectable levels of anti‐D Ig more than 12 weeks after administration, even when 300 μg of anti‐D Ig was administered in a single gift; 29 therefore, anti‐D Ig levels may drop too low if a pregnancy exceeds 42 weeks 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…The postmaturity risk factor might be explained by insufficient levels of preventive anti‐D Ig, after a single gift of 1000 iu (200 μg) in week 30 of pregnancy, in addition to the obvious immunogenic effect of prolonged exposure to fetal cells. Several studies showed undetectable levels of anti‐D Ig more than 12 weeks after administration, even when 300 μg of anti‐D Ig was administered in a single gift; 29 therefore, anti‐D Ig levels may drop too low if a pregnancy exceeds 42 weeks 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…24 Based on assumptions of circulating maternal plasma volume and extravascular fluid, this dose would yield a circulating plasma concentration of 2.4 ng/mL. 25,26 This minimum concentration is based on the average circulating blood volume in pregnant women and therefore does not account for inherent interpatient variability; nevertheless, 25 mg of RhIG per milliliter of D-positive RBCs is the clinical rule of thumb for RhIG dosing. Pharmacodynamic analyses of the clearance of RBCs against a constant dose of RhIG have shown that clearance is nonlinear across a range of RBC volumes, indicating that the standard RhIG:RBC ratio (25 mg to 1 mL) is not appropriate in all situations.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Several studies showed undetectable levels of anti-D Ig more than 12 weeks after administration, even when 300 lg of anti-D Ig was administered in a single gift; 29 therefore, anti-D Ig levels may drop too low if a pregnancy exceeds 42 weeks. [30][31][32] RBC transfusion is a less obvious factor contributing to RhD immunisation. Most likely, the RhD-negative RBCs have been given in all cases, as false-negative typing of donors is extremely rare.…”
Section: Discussionmentioning
confidence: 99%